Isolation and characterization of carcinogenic chromium reducing staphylococcus sciuri from tannery effluent of Hazaribag area - Hira, Tanjina Afrin (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.